Feasibility Analysis of Timber Sales Business Reviewed from Financial Aspects (Case Study of UD. Langgeng Jaya in Tawangsari Village, Jombang) - Rania Ningsih; Abdur Rohman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The furniture industry is an industry that converts wood into processed wood in the form of goods such as tables, chairs, cupboards, etc. Demand for processed wood is increasing along with population growth. The financial feasibility of UD Langeng Jaya was the focus of this research for five years, namely from 2017 to 2021. This location was chosen deliberately because there had been no previous research at UD. Langgeng Jaya is one of the wood sales industries that is currently developing. The data analysis used is the calculation of Net Present Value (NPV), Payback Period (PP), and Break Event Point (BEP). The results of the research show that UD Langgeng Jaya in Tawangsari Village, Mojowarno District, Jombang Regency, is financially feasible to develop in terms of Net Present Value (NPV) of IDR 2,742,319,730,- > 0, Payback Period (PP) for wood sales is 1 year, 9 months 7 days and the Break Even Point for sales of UD Langgeng Jaya wood is IDR 3,123,716,-, while the breakeven point for sales of beams and wood is 51 pieces.